Design and experimental validation of a metamaterial solution for improved noise and vibration behavior of pipes. (1st September 2019) - Nateghi, A.; Sangiuliano, L.; Claeys, C.; Deckers, E.; Pluymers, B.; Desmet, W.
Abstract: This paper investigates a metamaterial solution for efficient vibration attenuation and acoustic radiation reduction of an aluminum pipe. To this end, using unit cell predictions, locally resonant structures are designed to have a pronounced flexural resonance frequency at the vicinity of a dominant vibration mode of the pipe. A direct approach of the Bloch-Floquet theorem is adopted to provide the dispersion relation representing wave motion in an infinite metamaterial pipe. Using these wave dispersion relations, the frequency range of the stopband zone created by the metamaterial solution is predicted. The dynamic behavior of the finite counterpart is predicted using the Finite Element Method (FEM). The resonant structures are produced from polymethyl methacrylate (PMMA) panels and are added to the host structure. In order to properly characterize both the vibrational behavior of the metamaterial pipe and the acoustic radiation from its wall, impact tests using roving hammer technique is performed on the pipe and both accelerations and acoustic pressures are measured at different locations. The experimental results show a pronounced stopband zone created by the addition of a few rows of resonant structures. Moreover, comparisons between the measurements and numerical predictions show a good agreement.